Analisis Makna Syair pada Lagu Soka Selen Naman Tukan 2 dalam Tarian Dolo-dolo Larantuka - Labina, Yasinta; Jama, Karolus B.; Djokaho, Margareta P.E (Jurnal Lazuardi, 2025)
The focus of this study is to examine the meaning of the lyrics of the song "Soka Selen Naman Tukan 2" which accompanies the Larantuka dolo-dolo dance. This study aims to describe the meanings contained in the song "Soka Selen Naman Tukan 2" by Estrata Band. The theory used in this study is Paul Ricouer's hermeneutic theory. The method used in this study is a qualitative descriptive method that emphasizes the depth of information. The data source in this study is the song "Soka Selen Naman Naman Tukan 2" by Estrata Band. Based on the results of the study, the researcher found three main meanings contained in the song "Soka Selen Nman Naman Tukan 2". First, social meaning which includes the values ​​of togetherness, solidarity, entertainment, family ties, steadfastness to promises, emotional meaning, brotherhood, and sadness and disappointment. Second, cultural meaning which includes cultural identity, cultural expression through dance, cultural customary space, and traditional values ​​in economic and marriage aspects. Third, aesthetic meaning related to musical beauty and artistic expression in songs. From several meanings, the researcher concluded that the most dominant social meaning in the song "Soka Selen Nman Naman Tukan 2". Based on the findings of this study, it is expected to be a reference for further research. As well as enriching the literature and public knowledge that regional songs have deep meanings in each of their lyrics.